2015
DOI: 10.9734/bmrj/2015/16696
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antbiogram of Bacterial Isolates Causing Urinary Tract Infections at Federal Teaching Hospital Abakaliki I (FETHA I)

Abstract: Aims: This study is aimed to ascertain the prevalence and antibiogram of bacterial isolates causing urinary tract infection in Federal Teaching Hospital Abakaliki I (FETHA I) with the view to establishing a base line for the cautious use of antibiotics in the hospital. Study Design: Cross sectional. Place and Duration of Study: This study was carried out at Federal Teaching Hospital Abakaliki I (FETHA I) within the period of August to December, 2014.Methodology: One thousand patients (500 males and 500 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
9
12
2
Order By: Relevance
“…Those who were single at the time of the study had the highest prevalence of 64%, followed by those who were married -32%, while widows/widowers had 4%. This is similar to a previous report [25] chich reported that single individuals had the highest prevalence (44%), followed by those who were married (27%), divorced/separated (18%) and widows/widowers (11%). His is contrary to a study that reported the highest prevalence of UTIs among married women (66%), followed by those who were single (24%) [32].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Those who were single at the time of the study had the highest prevalence of 64%, followed by those who were married -32%, while widows/widowers had 4%. This is similar to a previous report [25] chich reported that single individuals had the highest prevalence (44%), followed by those who were married (27%), divorced/separated (18%) and widows/widowers (11%). His is contrary to a study that reported the highest prevalence of UTIs among married women (66%), followed by those who were single (24%) [32].…”
Section: Discussionsupporting
confidence: 92%
“…With respect to occupation, students showed the highest prevalence(58%), followed by civil servants (16%), traders (14%) and the unemployed (8%), while farmers had the least prevalence (4%). This is similar to a report by [25] that showed studentsas having the highest prevalence rate (42%), followed by civil servants (30%), small traders (15%), and casual labourers who showed the least prevalence (13%). This report is not in agreement with findings in [33] where amall traders showed the highest prevalence rate (33%), followed by casual labourers (30%), civil servants (21%), and students showed the least (17%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Worldwide, about 150 million people are diagnosed with UTI each year. 2 More than 95% of urinary tract infections are caused by a single bacterial species. E. coli is the most frequent infecting organism in acute infection.…”
Section: Introductionmentioning
confidence: 99%